APLIKASI PROSES BIOFILTRASI DAN ULTRA FILTRASI UNTUK PENGOLAHAN AIR MINUM - Said, Nusa Idaman (Center for Environmental Technology, 2006)
To reduce the organic substance and ammonia in raw water hence raw water from river have to be processed by pretreatment prior to main processing unit. One of the alternatives is biological treatment using submerged biofilter which filled with honeycomb plastic supporting media. Research conducted by operating continuous flow biofilter reactor wich filled with honeycomb plastic supporting media. The size of biofilter reactor is 59 cm x 30 cm x 210 cm, with total volume 371.7 litres.Ã‚Â The research was conducting by continuous operation under condition 4 hours, 3 hours, 2 hours and 1 hour retention time.Ã‚Â The result of experiment shows that within the biofilter process under conditions 4 hours, 3 hours, 2 hours and one hour retention time, the removal efficiency of organic substance were 67.27 %, 53,89 5,45.70 % and 30.92 % respectively. And the removal efficiency of ammonia under conditions 3 hours, 2 hours and one hour retention time were 73.59 %, 67.98 %, and 48.74 % respectively. The longer retention time has resulted in higher removal efficiency. By combining biofiltration process with ultra fltration (UF) membrane technology, hence will be got technological alternative of drinking water process which able to degrade an organic matter and ammonia without chemicals instead of convensional process.Ã‚Â Ã‚Â Kata Kunci : biofiltasi, membran, ultra filtrasi, air minum.Ã‚Â Ã‚Â Ã‚Â